Identity Politics and Political Behavior of Kiai in Tasikmalaya City: Case Study of Religious, Kinship and Regional Identity - Yuningsih, Siti Hadiaty; binti Abdullah Suhaimi, Nurnisaa; Kalfin (Communication in Research and Publications (CRP), 2023)
This research examines the influence of political identity, especially religious, kinship and regional identity, on the political behavior of kiai in Tasikmalaya City ahead of the General Election. Data was obtained through surveys and interviews with respondents from kiai circles in the area. The research results show that religious identity has the greatest influence on kiai's political behavior, followed by kinship identity, and then regional identity. Simultaneously, these three political identity factors also have a significant influence on kiai's political behavior. This research provides a better understanding of the complexity of identity politics in the context of kiai in Tasikmalaya City.